2018
DOI: 10.1007/s10792-018-0965-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and topographical characteristics of keratoconus in patients with refractive errors in the Egyptian delta

Abstract: Keratoconus was found in 1.12% of patients seeking refractive surgery, with no gender preference. Most cases had bilateral affection. Astigmatism was the most common refractive error to be associated with keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 23 publications
8
25
0
Order By: Relevance
“…The association between KC and allergic conjunctivitis is controversial; however, most studies have reported a firm association between allergy with eye rubbing and keratoconus. 17 In our study, we found that the percentage of subclinical KC in males 6.8% was significantly higher than in females 2.8%. Some studies in the literature have reported a higher prevalence of KC in males.…”
Section: Dovepresssupporting
confidence: 42%
See 2 more Smart Citations
“…The association between KC and allergic conjunctivitis is controversial; however, most studies have reported a firm association between allergy with eye rubbing and keratoconus. 17 In our study, we found that the percentage of subclinical KC in males 6.8% was significantly higher than in females 2.8%. Some studies in the literature have reported a higher prevalence of KC in males.…”
Section: Dovepresssupporting
confidence: 42%
“…4 Prevalence of KC is higher in the Middle East than in other areas, as proved by literature. 9,10,[14][15][16][17] This might be due to the high incidence of chronic allergies and spring catarrh. 17 In our study, VKH was reported in 35% of cases with subclinical KC, which is comparable to the value obtained by Omar & I.A.N who reported a 37.5% prevalence of VKC in KC eyes in Egyptian children with myopia.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…All articles were published between 2007 and 2020, with the majority (11) published within the last 5 years, i.e., 2016-2020. Five of the studies were conducted in Egypt, [32][33][34][35][36] two in South Africa, 37,38 two in Kenya, 39,40 one in Sudan, 41 one in Ghana 42 and one in Nigeria. 43 Two studies were conducted in allergic conjunctivitis patients, 33,39 four on exclusively keratoconus patients, 37,[40][41][42] one in patients seeking contact services, 38 one in pre-LASIK patients, 36 one in refractive patients 32 and one in a student population.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the studies were conducted in Egypt, [32][33][34][35][36] two in South Africa, 37,38 two in Kenya, 39,40 one in Sudan, 41 one in Ghana 42 and one in Nigeria. 43 Two studies were conducted in allergic conjunctivitis patients, 33,39 four on exclusively keratoconus patients, 37,[40][41][42] one in patients seeking contact services, 38 one in pre-LASIK patients, 36 one in refractive patients 32 and one in a student population. 43 Eleven (91.7%) were hospital-based studies 32,33,[36][37][38][39][40][41][42] and one was a school-based study.…”
Section: Resultsmentioning
confidence: 99%